Analyzing the Risk-Return Tradeoff in Commercial Banks' Common Stock: A Case Study of Nepalese Banks - Thapa, Narad Kumar; Modi, Devendra Kumar (International Research Journal of MMC, 2024)
This study investigates the risk-return tradeoff in the common stock of Nepalese commercial banks over a five-year period from 2018/19 to 2022/23. By analyzing financial data from four prominent banks listed on the Nepal Stock Exchange (NEPSE) i.e. Global IME Bank Limited (GBIME), Nepal Investment Mega Bank (NIMB), Nabil Bank Limited (NABIL), and Kumari Bank Limited (KBL). The study depends on the closing prices of these four commercial banks, which were generously provided through the NEPSE Index and annual general meeting (AGM) reports of each respective bank. The research aims to provide a comprehensive understanding of their risk profiles and expected returns using the Capital Asset Pricing Model (CAPM). The study employs descriptive statistics like mean, standard deviation, coefficient of variation, and maximum/minimum returns. The findings reveal significant variations in performance and risk levels: GBIME and KBL show positive average returns with high volatility, whereas NIMB and NABIL exhibit negative average returns, indicating losses. GBIME’s stock is slightly less volatile than the market, while NIMB’s low beta suggests it is suitable for conservative investors. NABIL’s and KBL’s higher betas indicate more volatility, appealing to high-risk tolerant investors. The study underscores the importance of portfolio diversification and continuous monitoring of market conditions for informed investment decisions. These insights are valuable for investors, financial regulators, and policymakers in developing effective risk management strategies and enhancing financial stability in Nepal's banking sector.